Gastos municipais com saúde: estrutura e impacto dos medicamentos "Genéricos" - Thiago Caliari Silva (2009)
With the promulgation of the Federal Constitution of 1988, the federal government delegated greater powers to the states and cities in actions that regard to public health policies. In this context, the goal of the dissertation is to study the structure of spending on health of cities and the impact that the public policy of generic drugs had in the spent those cities. The work is divided into two articles. At first, the goal is to study the municipal intervention on health policies especially noting the political pressure - from directing partisan - and institutional pressures - from federal government. Through the techniques of decomposition of differential and quantile regressions selected some determinants of municipal spending in the years 2002 and 2006. As key results, we find little relevance in the partisan direction and, before that, which seems to have become more important in that direction is the institutional pressure via Constitutional Amendment 29, which determined floor of their own resources spent by the cities. In the second article, we studied the impact of the "law of generics" in these municipal spending in line medicines for the period 2000 to 2005. Initially show that these products have a negative correlation - and significant - with the price level of the sector of drugs. After that finding, with a model of panel data, we found trend of growth in real spending of cities in line drugs by 2004 and a decrease for 2005. Still, the influence of the participation of generics in the price index in the same period also decreased, which confirms the results found. This drop may signal a certain exhaustion of the strategy of inexpensive generic drugs way with regard to its effect price. It follows therefore that the generic drugs resulted in lowering short-term, but for the maintenance of falling prices and improving the welfare pharmacist the government should invest in new public policies.